Analysis of Improving Teacher Discipline in Teaching by Superviing the Head of Madrasah MTs Bukhari Labuhanbatu - Dwina Putri; Anggili Pratama; Suryatik Suryatik; Ali Sadikin Ritonga; Santi Erika (Universitas Muhammadiyah Enrekang, 2022)
This study aims to reveal how